(untitled) (KYAMC Journal, 2024)
Background: Suicide is one of the leading causes of death in many countries and also a major public health concern. When a person dies by suicide the effects are felt by Family, Friends, and communities. The number of suicidal deaths is increasing worldwide day by day and Bangladesh is also facing this situation alarmingly. Objective: To evaluate the Socio-demographic profile of suicidal deaths. Materials and Methods: This cross-sectional study was carried out at Manikganj sadar hospital mortuary, from January 2019 to December 2019.Total 133 suicidal death cases were collected by using a pre-designed format from mortuary register book. The inquest report provided comprehensive information about the deceased. Postmortem examinations documented the method of suspension used and in cases of poisoning, chemical analysis was conducted to determine the type of poison. Results: During this study majority of the deceased were Female (50.38%). The age distribution of the deceased from 01 year to above 51 years, the highest occurrence observed in the age group 11-20 years (33.08%). Most of the deceased were House wife (40.00%). Majority of deceased were Muslims (88.72%). Total 30.08% cases were reported under Manikganj sadar Thana. The most prevalent technique observed for suicide were by Hanging (65.41%) and common consumption of poison is Organo-phosphorous compound (OPC) (65%). Conclusion: The collected data has the potential to facilitate the identification of individuals who are at an elevated risk of engaging in suicidal behaviors. Moreover, this information can be effectively used to support individuals through the implementation of a comprehensive nationwide suicide prevention initiative that adopts a collaborative and interdisciplinary approach. KYAMC Journal Volume: 14, No: 04, January 2024: 210-214.